Is there a Profile of Spontaneous Seizure-Alert Pet Dogs? A Survey of French People with Epilepsy - Catala, Amélie (Animals (Basel), 2020)
SIMPLE SUMMARY: Very little is known about dogs that could alert their owner of an impending epileptic seizure. Here, we explored the profiles of untrained dogs that spontaneously show seizure-related behaviors. Using a self-reporting questionnaire, we found that these dogs do not have a particular profile (e.g., sex, breed, age, epilepsy of the owner), but bonding is perceived as better when the dog alerts compared to a dog who does not alert. Personality traits helped discriminate between these two types of dogs; seizure-alert dogs were scored higher for Motivation, Training Focus and lower in Neuroticism than non-alerting dogs. In addition, we reported alert-related behavior characteristics (e.g., the dogs that alerted the more frequently stayed close and stared at their owner when he/she had a seizure). Our results are in line with the existing literature and help further the understanding of seizure-alert dogs. In particular, we suggest that some personality traits could be a basis for the selection of future assistance dogs. ABSTRACT: Despite controversies and the lack of research, dogs are empirically selected and trained to perform as service dogs, in relation to the dogs’ and future owners’ characteristics. We assessed the characteristics of both humans and dogs in an unbiased population (not selected or trained) of spontaneous seizure-alert by pet dogs and investigated whether we could replicate previous findings. We addressed a self-reporting questionnaire to French people with epilepsy. We analyzed the general characteristics of the humans and pet dogs and their behaviors that could alert their owner before a seizure. In addition, we used the Monash Canine Personality Questionnaire refined to evaluate pet dogs’ personality through five different traits, and the Monash Dog-Owner Relationship scale to assess human–dog relationships. In line with previous reports, we found no particular factor, either pet-, people- or epilepsy-related that could be associated with the presence or absence of alert behaviors. Alert behaviors and circumstances were explored and three different alert patterns emerged. In terms of personality, seizure-alert pet dogs scored significantly higher than non-alerting dogs for the traits “Motivation” and “Training Focus” and lower for “Neuroticism”. The owner–dog bond score was significantly higher for seizure-alert dogs than for non-alerting dogs.